The effect of transformational leadership on small and medium enterprises performance of UAE: the mediation roles of employee creativity and organization innovation - Ali Al Khazraji, Duha Hashim (2022)
Today, small and medium enterprises (SMEs) become a vital asset for almost all countries in the world and represent a dynamic sector of the global economy. In the United Arab Emirates (UAE), SMEs is the pillar of economic growth in the last decades. While leadership has been proven to raise the profitability and growth among SMEs, the scenario in the UAE is not encouraging, lots of SMEs are struggling to maintain business on the long term, and they are unable to benefit from innovation or hire creative workforce. The reality shows that SMEs in UAE are weak against crises and tough competition. Unsuccessful leadership style was the main cause for continuous losses and failure which forced them to shut down the business or downsize their activities and workforce. Despite the wealth of studies on this topic, there is lack of empirical studies that report the solutions to these problems in the UAE. Hence, the aim of this study is to examine the significance of relationships between transformational leadership, organization innovation, employee creativity, and SME business performance, as well as the mediation roles of organization innovation, employee creativity. Quantitative methods have been deployed to examine these relationships. The population equal 11023 of SMEs working in in Abu Dhabi, the respondents are the executive managers. SMEs worked in information and communication, manufacturing, education, financial and insurance, professional scientific and technical are included in the survey procedure. Simple random sampling technique was used to distribute the questionnaires during the survey phase. A sample of 441 SMEs was specified for survey and collecting the data for the analysis. The results revealed that all direct and indirect relationships are significant, whereas organization innovation, employee creativity partially mediate the relationship between transformational leadership and SME business performance. This study makes several theoretical contributions to the topic of transformational leadership and organizational performance. Whereas the creativity of employees seems to be a key source of innovation particularly in SME, it become vital resources to achieve economic growth in the market and sustainable profitability. Accordingly, SMEs should focus on leaders who have certain traits, such as idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration to raise profitability and business growth in UAE market. The findings of this study will benefit the SME Council of UAE to empower small and medium-sized projects and businesses including representatives from government bodies, and developing strategic plans and policies for small firms, setting the necessary rules and regulations to enhance the coordination between the UAE’s National Program for SMEs and following-up the program’s performance indicators.